The Effects of Dietary Mulberry Leaves (Morus alba L.) on Chicken Performance, Carcass, Egg Quality and Cholesterol Content of Meat and Egg - PANJA, Paichok (Walailak Journal of Science and Technology (WJST), 2013)
Experiment I (Broilers) The experimental design was completely randomized. Two hundred and forty of 3 week old male broilers were divided into 5 groups with 4 replicates of 12 birds each. The protein and metabolizable energy content of basal diets were 20 % and 3,000 kcal/kg, respectively. The basal diets were supplemented with mulberry leaves at 0, 0.5, 1.0, 1.5 and 2.0 % of diet. The results demonstrated that feed intake, weight gain, feed efficiency, nitrogen and energy intake were not significantly different among treatments (P > 0.05). The carcass quality showed that carcass weight, dressing percentage and percent of abdominal fat pad were also not significantly different (P > 0.05). The blood cholesterol and triglyceride were significant (P < 0.05) lower at higher levels of mulberry leaves. However, the cholesterol content in thigh meat was not significantly different among treatments (P > 0.05). Experiment II (Layers) The experimental design was completely randomized and two hundred of 27 week old laying hens were divided into 5 groups with 4 replicates of 10 birds each. The protein and metabolizable energy content of basal diet were 16 % and 2,750 kcal/kg, respectively. The basal diets were supplemented with mulberry leaves at 0, 0.5, 1.0, 1.5 and 2.0 % of diet. The results found that feed intake, egg weight, egg mass, and egg quality were not significantly different among treatments (P > 0.05). The blood cholesterol was found to decrease (P < 0.05) at 0.5, 1.0 and 2.0 % of mulberry leaves inclusion. Likewise, triglyceride was also found to decrease (P < 0.05) at 0.5 to 1.5 % of inclusion. In addition, yolk cholesterol content was found to decrease and was significantly different (P < 0.05) at 2 % of inclusion.